Hemorrhagic disease of the newborn: modern approaches to diagnosis, prevention and treatment - E. M. Rashkova; A. A. Shakirova; H. A. Sarkisyan; L. A. Levchenko; S. V. Cherkasova; E. I. Shabelnikova (Лечащий Врач)
Background. Hemorrhagic disease of the newborn is a pathological condition in newborns and children during the first months of life, caused by vitamin K deficiency of dependent blood coagulation factors and manifested by increased bleeding. The incidence of hemorrhagic disease of the newborn varies in different regions of the world, in Russia, according to the literature data, it ranges from 0.25 to 1.7%. Hemorrhagic disease of the newborn is characterized by the development of bleeding and hemorrhage, which negatively affect the function and further development of a number of organs and systems of the child, especially the central nervous system and the gastrointestinal tract. Based on the etiology of the development of the disease described above, HDN is classified into primary (idiopathic) and secondary. Depending on the age of onset, early is distinguished – it manifests itself in the first 24 hours of life, classical – develops on the 2-7th day and late, manifesting itself after 1 week of life (rarely occurs at the age of up to 6 months of life, and some authors indicate the age children under 1 year of age) hemorrhagic disease of the newborn forms. The key priority of neonatologists is to single out from the number of born children, newborns who are at risk for HRD for the purpose of prophylactic administration of vitamin K to them, which will prevent severe undesirable consequences of the disease. A genetic study using logistic regression analysis confirmed a higher risk of intraventricular hemorrhages in newborns with polymorphisms in the VKORC1 genes, which is responsible for the binding of vitamin K1 to cysteine, and thus for a decrease in its concentration in carriers of this gene. Despite the variability in approaches to doses, methods and timing of administration, parenteral administration of vitamin K is the only reliable and preferred way to prevent this disease. In the case of the development of hemorrhagic disease of the newborn, modern approaches to the diagnosis and treatment of this pathology have been developed.Results. The article presents modern approaches to the prevention, diagnosis and therapy of vitamin K-dependent hemorrhagic disease of the newborn.